Community-based Disaster Risk Reduction in Patakbanteng Village: Lessons from Christchurch, Sirnajaya, and Barangay Banaba - Saadah, Kholifatus; Pradana, Christiano Disa (Prodi Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Abstract Natural disasters are unavoidable events. Moreover, they transcend national boundaries, so the solutions should be transnational. Therefore, several mechanisms must be put in place to address these inevitable events to prevent widespread casualties. To mitigate the risks posed by natural disasters, the United Nations Office for Disaster Risk Reduction (UNDRR) issued the Sendai Framework for Disaster Risk Reduction (2015-2030). While the Sendai Framework is designed internationally, its implementation must involve local levels, such as urban and rural areas. This is directly related to the impacts experienced, which are often faced and borne by the lowest levels. This paper will discuss the role of rural communities in meeting the four priorities of the Sendai Framework. Community-based disaster risk reduction (CBDRR) has been implemented in several areas, including Christchurch, New Zealand, Sirnajaya Village in West Java, Indonesia, and Barangay Naraba, Philippines. Based on the experiences of these three regions, the author wanted to determine whether Patakbanteng Village in Wonosobo, Central Java, already had the points listed in the CBDRR. This is directly related to Patakbanteng Village's location in a landslide-prone area. The author chose CBDRR because the impact of disasters will be felt at the local level. Findings from the three locations suggest that embedding Sendai principles into village governance, local resource mobilization, and indigenous knowledge systems is critical to strengthening resilience. This paper also explains the importance of villages as areas that are not only recipients of international frameworks but also play a crucial role in ensuring the successful implementation of these frameworks. Keywords: Disaster risk reduction, Sendai Framework, Community-based, Patakbanteng, Christchurch, Sirnajaya, Barangay Naraba, Landslide-prone Area